CNTs@γ-Fe2O3@C composite electrode for high capacity lithium ion storage. (26th July 2018) - Jiang, Xiaotong; Guo, Wenlei; Lu, Pengyi; Song, Dan; Guo, Anran; Liu, Jiachen; Liang, Ji; Hou, Feng
Abstract: Electrode materials with high specific capacity and cycle stability are the key factors that determine the overall performance of lithium ion batteries (LIBs) for new smart electronic device, and such materials with high performance are still challenging. Here, we report a composite material Carbon nanotube @ Iron oxide @ Carbon (γ-CNTs@γ-Fe2 O3 @C) with coaxial cable structure in hydrothermal method with the assistance of glucose. The as-prepared composite materials show superior electrochemical properties with good rate capability and excellent cycling performance, which show the great potential of CNTs@γ-Fe2 O3 @C for practical production and application in energy devices. Highlights: A rationally-designed coaxial structure is obtained through a facile two-step process. The structure is highly controllable by simply tuning the synthetic parameter. This unique structure can effectively enhance the performance of the materials. It has very high capacity retention of 97.67% after 150 cycles at 2 A g −1 .